2022
DOI: 10.1186/s12909-022-03526-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the BOPPPS model and traditional instructional approaches in thoracic surgery education

Abstract: Background BOPPPS (bridge-in, learning objective, pretest, participatory learning, posttest, and summary) is a student-centered modular teaching model that improves classroom teaching effectiveness. This study’s primary aim was to explore whether the BOPPPS model has advantages over traditional instructional approaches in teaching lung cancer courses to clinical medical interns. Methods A total of 88 students majoring in clinical medicine of Shando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…The results of this study showed that the CBL-BOPPPS model is signi cantly better than TL in improving team assistance, problem-solving skills, course interest, and clear learning objectives (P <0.01). BOPPPS is a closed-loop teaching model, that guides students to participate in classroom learning, stimulating students' enthusiasm [26], enhancing the students' comprehensive ability [12], and improving their autonomous learning competencies and critical thinking ability [13,27]. In this study, the introduction of typical clinical cases in the "Bridge-in" unit has a positive effect on improving student's learning interest and active thinking[28], which is more helpful for students to clarify their learning objectives in the "Objective" unit [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of this study showed that the CBL-BOPPPS model is signi cantly better than TL in improving team assistance, problem-solving skills, course interest, and clear learning objectives (P <0.01). BOPPPS is a closed-loop teaching model, that guides students to participate in classroom learning, stimulating students' enthusiasm [26], enhancing the students' comprehensive ability [12], and improving their autonomous learning competencies and critical thinking ability [13,27]. In this study, the introduction of typical clinical cases in the "Bridge-in" unit has a positive effect on improving student's learning interest and active thinking[28], which is more helpful for students to clarify their learning objectives in the "Objective" unit [29].…”
Section: Discussionmentioning
confidence: 99%
“…Real cases and scenarios are bene cial in encouraging students to apply theoretical knowledge to case analysis [10], developing students' problem-solving ability [4], and facilitating team assistance [10]. The BOPPPS design emphasizes students' active participatory learning and has obvious advantages over traditional teaching in improving learning initiative, analytical ability, clinical thinking ability, and self-study ability [6,12]. These may explain why the learning outcomes of CBL-BOPPPS are more effective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Central to BOPPPS is its emphasis on student-centered instruction within an innovative and interactive learning setting. BOPPPS has been applied in health services management teaching, [2] lung cancer courses for clinical medical interns [3] and dental materials courses for predoctoral dental students. [4] By thoughtfully designing the teaching process and reinforcing closed-loop teaching units, it proves beneficial in fostering students’ enthusiasm for learning, enhancing their learning efficiency, and nurturing their capacity for innovative thinking.…”
Section: Introductionmentioning
confidence: 99%
“…By creating a sense of ownership and excitement for learning, BOPPPS encourages students to take an active role in their education. This innovative approach has found applications in a variety of medical disciplines, including ophthalmology 8 , health services management 9 , thoracic surgery education 10,11 , physiology education 12 , and Dental Materials Education 13 , and others.…”
Section: Introductionmentioning
confidence: 99%